Sers detection of penicillin g using magnetite decorated with gold nanoparticles - Pinheiro, Paula (2017)
Sensitive and reliable procedures for detecting vestigial antibiotics are of great relevance for water quality monitoring due to the occurrence of such emergent pollutants in the aquatic environment. As such, we describe here research concerning the use of multifunctional nanomaterials combining magnetic and plasmonic components. These nanomaterials have been prepared by decorating magnetite nanoparticles (MNP) with colloidal gold nanoparticles (Au NPs) of distinct particle size distributions. Several analytical conditions were investigated in order to optimize the surface enhanced Raman scattering (SERS) detection of penicillin G (PG) dissolved in water. In particular, the dependence of the SERS signal by using distinct sized Au NPs adsorbed at the MNP was investigated. Additionally, microscopic methods, including Raman confocal microscopy, were employed to characterize the SERS substrates and then to qualitatively detect penicillin G using such substrates. For example, magnetic–plasmonic nanocomposites can be employed for magnetically concentrate analyte molecules and their removal from solution. As a proof of concept, we applied magneto-plasmonic nanosorbents in the removal of aqueous penicillin G and demonstrate the possibility of SERS sensing this antibiotic.